FRI0326 Efficacy and Safety of Tabalumab, an Anti-B Cell Activating Factor Monoclonal Antibody, in Patients with Rheumatoid Arthritis Who HAD an Inadequate Response to Methotrexate Therapy: Results from A Phase 3 Multicenter, Randomized, Double-Blind Study. (10th June 2014) - Smolen, J.S.; Weinblatt, M.E.; van der Heijde, D.; Rigby, W.F.; van Vollenhoven, R.; Bingham, C.O.; Veenhuizen, M.; Gill, A.; Zou, H.; Komocsar, W.; Berclaz, P.-Y.; Ortmann, R.; et al.
Abstract : Background: Tabalumab is a monoclonal antibody that neutralizes membrane-bound and soluble B cell activating factor (BAFF). Objectives: Evaluate efficacy and safety of tabalumab, in RA pts who had an inadequate response to methotrexate (MTX) therapy, in a randomized, double-blind, placebo-controlled study. Methods: 1041 RA pts (ITT population) were enrolled in this 52-wk study evaluating 2 subcutaneous (SQ) tabalumab doses (120mg every 4 wks [120/Q4W] or 90mg every 2 wks [90/Q2W]) vs placebo (PBO). At wk 0, pts received a SQ loading dose that was 2 times the treatment dose (240mg, 180mg, or PBO). Eligible pts had moderate-severely active RA despite ongoing MTX. Primary endpoints included ACR20 and HAQ-DI at 24 wks, and change in mTSS at 52 wks. This study was terminated early due to futility. Results: The ITT population was mostly female (84.2%), and seropositive (RF and/or anti-CCP, 95%) with a mean age of 53.2 yrs, mean RA diagnosis of 6.8 yrs, and DAS28-CRP of 5.6±1.0 (mean ± SD). At wk 24 in the efficacy population (ITT population excluding pts on <10 mg/wk of MTX, n=997), there were no significant differences among the 120/Q4W, 90/Q2W, and PBO groups in the percentage of pts achieving ACR20 (NRI; 29.7%, 32.8%, 25.1%). There was no significant difference among the 120/Q4W, 90/Q2W, and PBO groups in structural progression defined as change from baseline in mTSS (mean ± SD) at wk 52 (1.5±4.9, 0.9±3.8, 1.7±5.3). A modest difference was observed in wk 24 HAQ-DI results (mean ± SD) in the 90/Q2W group (mBOCF; 1.2±0.6) vs PBO (mBOCF; 1.3±0.7) [p=0.005]; no difference was observed in the 120/Q4W group (mBOCF; 1.3±0.6). After 52 wks, changes in CD3-CD20+ B cells in the 120/Q4W, 90/Q2W, and PBO groups were −15.0%, −18.8%, and 5.3%. Changes in immunoglobulin levels in the 120/Q4W, 90/Q2W, and PBO groups were: IgM (−16.3%, −19.4%, −0.1%), IgA (−11.4%, −4.7%, 1.2%), and IgG (−8.6%, −7.8%, 0.1%). Safety was evaluated in all randomized pts who received ≥1 dose of study treatment (n=1038). Discontinuations due to an AE were similar across the 120/Q4W, 90/Q2W, and PBO groups (4.3%, 3.5%, 2.9%) as were TEAEs (54.2%, 50.7%, 53.7%) and SAEs (5.2%, 5.2%, 4.9%). For the 120/Q4W, 90/Q2W, and PBO groups, there was no difference in reports of AEs of interest: infections (24%, 23%, 26%); injection-site reactions (2.3%, 4.3%, 2.3%); and allergic/hypersensitivity events (4.3%, 3.5%, 4.6%). Three deaths occurred: 2 120/Q4W pts (sepsis, MI) and 1 PBO pt (MI). Conclusions: In this phase 3 study, tabalumab demonstrated no clinical efficacy despite evidence of biologic activity. There were no differences in reports of AEs of interest and no new or unexpected safety findings for RA pts receiving tabalumab. Disclosure of Interest: J. Smolen Grant/research support: Pfizer, Consultant for: Pfizer, Eli Lilly and Company, M. Weinblatt Consultant for: Eli Lilly and Company, Pfizer, Vertex, D. van der Heijde Consultant for: Eli Lilly and Company, AbbVie, Amgen, AstraZeneca, Augurex, BMS, Celgene, Centocor, Chugai, Covagen, Daiichi Sankyo Ltd, GlaxoSmithKline, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Vertex, W. Rigby Consultant for: Eli Lilly and Company, R. van Vollenhoven Grant/research support: AbbVie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, GSK, Janssen, Eli Lilly and Company, Merck, Pfizer, Roche, UCB, Vertex, C. Bingham III Grant/research support: Eli Lilly and Company, Consultant for: Eli Lilly and Company, M. Veenhuizen Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, A. Gill Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, H. Zou: None declared, W. Komocsar Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P.-Y. Berclaz Employee of: Eli Lilly and Company, R. Ortmann Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Lee Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company DOI: 10.1136/annrheumdis-2014-eular.1535